Pyroptotic Patterns in Blood Leukocytes Predict Disease Severity and Outcome in COVID-19 Patients - Tang, Yingkui; Zhang, Peidong; Liu, Qiuyu; Cao, Luyang; Xu, Jingsong (Frontiers in Immunology, 2022)
The global pandemic of COVID-19 has been lasting for 2 years and has already caused millions of deaths. As a critical innate immune method, pyroptosis's role in COVID-19 disease development is still debated, with some research claiming that it is beneficial and others claiming it is detrimental. Using transcriptomic data of blood leukocytes from acute respiratory distress syndrome patients (ARDS) with or without COVID-19, we found that COVID-19 patients exhibited enhanced pyroptosis levels. Based on unsupervised clustering, we divided 100 COVID-19 patients into two clusters (PYRcluster) according to the expression of 35 pyroptosis-related genes. Varied PYRclusters displayed different pyroptotic patterns and expressed different pyroptosis-related genes. PYRcluster2 exhibited higher immune levels and a better prognosis. The differences in pyroptosis between the two PYRclusters were confirmed by our constructed PYRscore. To better assist the clinical treatment of COVID-19 patients, we used LASSO regression to construct a prognostic model based on the differentially expressed genes between PYRclusters: PYRsafescore, which performed excellently. Finally, we explored the upstream transcription factors of different pyroptotic patterns and collected 112 compounds with potential therapeutic value in public databases.